Degradation of Whole Cottonseed and Grass Hay by the Ruminal Bacteria and Their Survival in the Presence and Absence of Gossypol in Culture - Ismartoyo (Research Perspectives of Microbiology and Biotechnology Vol. 6, 2024)
Whole Cottonseed (WCS) in vitro rumen incubation was applied to determine their nutrient and gossypol degradation characteristics and bacterial degradation profile in a consecutive batch culture system. It has been found that the presence of gossypol at 1 mM significantly depressed dry matter loss, gas production, and survival of mixed rumen microbes in culture. Mixed rumen microbes appeared to adapt to the presence of gossypol in culture. However, it is still unclear which of the rumen microbes were affected by the gossypol. Fractionation of the rumen microbial population was conducted to separate as much as possible, rumen bacteria from rumen protozoa and fungi. The fermentation of whole cottonseed (WCS), grass hay (GH) by the bacteria was then studied in the presence and absence of gossypol in culture. The results of this experiment showed that there were significant differences (p<0.01) in the rumen bacterial degradation of WCS, GH with and without gossypol. GH was the most degradable and WCS the least degradable of these substrates for rumen bacteria. Similarly, fermentation of GH resulted in higher (p<0.01) gas production than that of WCS and GH with gossypol demonstrating that bacterial fermentation was reduced. Rumen bacteria did not appear to adapt to the presence of 1 mM gossypol suggesting that they were severely affected by gossypol.